Pedagogical aspects of professional competence development of technical university students - Konstantin V. Trubitsyn; Olga Yu. Kalmykova; Vasily K. Tkachev (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper discusses the psychological and pedagogical aspects of the process of professional competence development of technical university students, associated with the increase in the requirements of employers to the portfolio of professional competencies of modern specialists. The authors discuss the problem of improving teaching methods and techniques; modernization of organizational forms and educational and methodological support for the professional competence development of technical university students on the example of the Heat and Power faculty of SamSTU. The paper stimulates a discussion about professional competencies, active and interactive teaching methods aimed at developing the ability of technical university students for self-development and self-study in order to effectively implement possible scenarios for their professional development trajectory. The aim of the study is to develop methodological recommendations to enhance the professional competence of students of the Heat and Power Faculty of Samara State Technical University, involving the use of modern educational approaches and improving the methodology for individualizing education at a technical university. The results of the study are achieved by solving the following tasks: conducting expert surveys (respondents: teachers and university students) to determine the most effective teaching methods; creating methodological materials. This study was carried out in several stages. Tasks of the theoretical stage include the analysis of the psychological and pedagogical aspects of the implementation of methods and organizational forms that ensure the effective formation of professional competence of students of a technical university. Tasks of the diagnostic stage of the study are conducting a questionnaire survey of students in order to assess the importance of the competencies necessary for successful professional activity; conducting a questionnaire survey of students and an expert survey of teachers in order to assess the significance of methods, methodological support and organizational forms of education at a technical university. The paper presents the results of surveys of students of the Heat and Power Faculty of Samara State Technical University and university teachers (2021-2023). The respondents of the expert survey were students of the advanced training program Management of the educational process: psychological and pedagogical competence of a technical university teacher and the retraining program Teacher of higher education of SamSTU Institute of Extended Education. The following methods were used in the study: expert survey, observation, questioning. The perspective of the research is the modernization of the methodology of individualization of education and educational and methodological support for the professional competence development of technical university students.